Metaphors and metonymies in the presidential debate between Pedro Castillo vs. Keiko Fujimori - Bardales Sihue, Rosa Milagros (2022)
Two days later, Francisco Sagasti assumed the presidency and was in charge of calling elections. Thus, in May 2021, the first electoral debate was held between the candidates who represent opposing ideologies and who passed to the second round: Pedro Castillo and Keiko Fujimori. In this article, we analyze metaphorical and metonymic expressions in the political debate, under the proposal of cognitive semantics (Lakoff and Johnson, 1980; Ruiz de Mendoza and Pérez Hernández, 2001), in order to explain how politics, health, the country, education and the economy were categorized in the Peruvian electoral campaign. The results of the research show that both politicians coincide in their vision of politics as a war, but differ in the way they understand the economy, health and education.